Acinetobacter tibetensis JSK8 and application thereof in degrading plastic
Patent Information
- Application Number
- CN202611029118.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-11-03
AI Technical Summary
In existing technologies, the degradation efficiency of plastics is low, the degradation conditions are harsh, the degradation strains are highly selective for plastic types, and secondary pollution may occur, which limits the practical application of microbial degradation of plastics.
Acinetobacter tsui JSK8 was used. This strain can degrade various plastics, including PHB, PLA, PET, and PE, at room temperature and pressure. The degradation of plastics was achieved by culturing it in MSM inorganic salt medium with an addition of 5% (v/v) and an OD600 value of 0.1.
Acinetobacter tsui JSK8 can achieve a PHB degradation efficiency of up to 10% within 45 days without strain modification or plastic pretreatment. The degradation method is simple, low-cost, and environmentally friendly, significantly improving the degradation efficiency of plastics.
Smart Images

Figure CN123027147A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bio-environmental protection technology, specifically relating to Acinetobacter tibetans JSK8 and its application in degradable plastics. Background Technology
[0002] Plastics are widely used due to their low cost, durability, and lightweight nature. However, plastic waste degrades into microplastics under various influences. These microplastics are difficult to degrade and accumulate in the environment, causing numerous harms to marine ecosystems and organisms, such as adsorbing pollutants, being ingested by organisms, and posing risks to human health. The degradation rate, intermediate processes, and ultimate ecological risks of polylactic acid (PLA) and polyhydroxybutyrate (PHB) in the natural environment are far more complex than imagined. Achieving "degradability" is highly dependent on environmental conditions, especially temperature and the types of microorganisms. In the natural environment, both materials are difficult to degrade rapidly and completely.
[0003] PLA degradation is extremely demanding. Under ideal conditions, in high-temperature (approximately 58°C) and high-humidity industrial composting facilities, PLA can completely degrade into water and carbon dioxide within about 180 days (6 months). However, in reality, once it enters the ocean, ordinary soil, or landfills, its degradation rate drops drastically, becoming almost as slow as traditional plastics. Experiments have shown that biodegradable plastic bags buried in residential greenbelts for three years have not yet completely decomposed.
[0004] PHB is more biodegradable than PLA, but the rate of degradation remains variable. Under ideal conditions in specific soils or activated sludge, degradation is very rapid, taking anywhere from a few days to a few weeks. Under natural conditions, it is generally considered to take about 120 days to 12 months to fully degrade in soil. However, in seawater, degradation time can extend to several years.
[0005] PLA and PHB undergo a microplastic phase before complete degradation, posing a potential risk to ecosystems and organisms. In the early stages of degradation, PLA breaks down into tiny, invisible fragments, temporarily causing pollution. Studies have shown that high doses of PLA and PHB microplastics can cause dose-dependent developmental toxicity in aquatic organisms. For example, nanoscale PLA particles can induce oxidative stress and genetic damage in insects. PHB microplastics may impair the growth and behavior of aquatic organisms.
[0006] Microbial degradation of plastics has become a key to pollution mitigation due to its environmentally friendly and biorecyclable advantages. However, there is limited research on this method. Currently, few microorganisms capable of degrading plastics have been discovered, and their degradation efficiency is generally low. Highly efficient degradation strains have yet to be found.
[0007] Current mainstream disposal methods, such as landfill and incineration, have significant environmental and efficiency problems. Utilizing microorganisms to degrade plastics is considered a promising green solution, but it currently remains primarily in the laboratory research stage and faces several major bottlenecks:
[0008] 1. Low degradation efficiency: This is a common problem faced by most degradation bacteria.
[0009] 2. Harsh Degradation Conditions: Many degrading bacteria require temperatures above 30°C to function actively. Maintaining such temperatures requires additional energy consumption, increasing costs and carbon emissions, which limits their application in natural environments (especially cold regions). Furthermore, strains may also have specific requirements regarding pH, nutrients, and other conditions.
[0010] 3. High selectivity for plastic type: A degrading bacterium is usually only effective against one or a few specific types of plastic.
[0011] 4. Potential secondary pollution: During the degradation of plastics, microorganisms may "promote the formation and release of microplastics and nanoplastics." Studies have found that just 10 mg of polystyrene tablets can generate millions of microplastics and nanoplastics within 30 days under the action of marine bacteria. These microplastics may pose new environmental risks. Summary of the Invention
[0012] In view of the problems in the prior art, the present invention aims to provide Acinetobacter tsui JSK8 and its application in degradable plastics.
[0013] The technical solution adopted by the present invention to achieve the above-mentioned technical objectives is as follows:
[0014] This invention provides Acinetobacter tibetensis JSK8, which was deposited on December 1, 2025, at the China General Microbiological Culture Collection Center (CGMCC) with accession number CGMCC No. 36830 and classified as Acinetobacter tibetensis.
[0015] Furthermore, the nucleotide sequence of the 16S rDNA of Acinetobacter tsuifolia JSK8 is shown in SEQ ID NO.3.
[0016] This invention also provides the application of Acinetobacter tibetans JSK8 in the degradation of plastics, including four types of plastics: polyhydroxybutyrate (PHB), polylactic acid (PLA), polyethylene terephthalate (PET), and polyethylene (PE).
[0017] Furthermore, the application includes culturing Acinetobacter tsuifolia JSK8 with plastic on a shaker at 28 °C and 121 r / min to achieve degradation.
[0018] Furthermore, using plastic as the sole carbon source in MSM inorganic salt medium, the bacterial culture of Acinetobacter tsui JSK8 was added at a concentration of 5% (v / v, volume ratio), and the bacterial culture OD... 600 The value is 0.1.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] A novel bacterial strain, Acinetobacter tibetans JSK8, has been discovered for the first time, capable of degrading four types of plastics: PHB, PLA, PET, and PE. This strain operates under mild conditions (ambient temperature and pressure), requiring no strain modification or plastic pretreatment. The degradation method is simple, low-cost, and environmentally friendly. Experiments have shown that without any strain modification, environmental alterations, or plastic pretreatment, this strain can achieve a PHB degradation efficiency of 10% within 45 days, demonstrating significant effectiveness. Attached Figure Description
[0021] Figure 1 The sample bacterial solution showed a concentration of 10. -2 10 -3 10 -4 Transparent rings formed by concentration gradient dilution coating on solid screening plates, Figure A: Front view of three plates, Figure B: Back view of three plates.
[0022] Figure 2 From Figure 1 The growth of strains selected from the plates on solid screening plates.
[0023] Figure 3 From Figure 2 The results of the third streak purification of single colonies selected from the plate on LB solid plates.
[0024] Figure 4 These are PCR electrophoresis results. M represents the molecular weight standard (100-1500bp) of a 100bp DNA Marker, brand: White Shark, catalog number: BL101A. Lanes JSK1, JSK3, JSK4, JSK5, JSK6, JSK7, and JSK8 correspond to the following values in sequence. Figure 3 Single colonies picked from each plate.
[0025] Figure 5 The results of BLAST alignment of 16S rDNA of strain JSK8 are shown.
[0026] Figure 6 Phylogenetic tree of strain JSK8 based on 16S rDNA.
[0027] Figure 7Phylogenetic tree of multiple core genes across the entire genome of strain JSK8.
[0028] Figure 8 The degradation efficiency (%) of strain JSK8 on PET, PE, PLA, and PHB plastics was compared at 15 days, 30 days, and 45 days.
[0029] Figure 9 The absorbance (A410) of strain JSK8 in MSM inorganic salt medium with PHB, PE, PLA, and PET as the sole carbon source.
[0030] Figure 10 The enzyme activity (U / mL) of strain JSK8 in MSM inorganic salt medium with PHB, PE, PLA, and PET as the sole carbon source.
[0031] Figure 11 The images show a comparison of scanning electron microscopy (SEM) images of plastic films before and after degradation. Image A: Blank control of PET plastic film cultured for 45 days without JSK8; Image B: Adhesion of JSK8 strain on the surface of PET plastic film after 45 days of culture with JSK8; Image C: Blank control of PE plastic film cultured for 45 days without JSK8; Image D: Adhesion of JSK8 strain on the surface of PE plastic film after 45 days of culture with JSK8; Image E: Blank control of PLA plastic film cultured for 45 days without JSK8; Image F: Adhesion of JSK8 strain on the surface of PLA plastic film after 45 days of culture with JSK8; Image G: Blank control of PHB plastic film cultured for 45 days without JSK8; Image H: Adhesion of JSK8 strain on the surface of PHB plastic film after 45 days of culture with JSK8.
[0032] Figure 12 Figure 1 shows the FTIR spectra of degradation products of strain JSK8 in PET, PE, PLA, and PHB. Figure 2 shows the degradation products analysis results for PET, PLA, PE, and PHB.
[0033] Figure 13 The degradation efficiency (%) of biodegradable plastics PET, PE, PLA, and PHB over 45 days under sterile and non-sterile conditions.
[0034] Figure 14To illustrate the formation of intermediate degradation products of biodegradable plastics PET, PLA, and PHB under sterile and microbial conditions (LC-MS), Figure a shows the LC-MS results for the PHB degradation intermediate product 3-hydroxybutyric acid standard; Figure b shows the LC-MS results for samples after 45 days of co-culturing with JSK8; Figure c shows the LC-MS results for the PLA degradation intermediate product lactic acid standard; Figure d shows the LC-MS results for samples after 45 days of co-culturing with JSK8; Figure e shows the LC-MS results for the PET degradation intermediate product BHET (dihydroxyethyl terephthalate) standard; Figure f shows the LC-MS results for samples after 45 days of co-culturing with JSK8; Figure g shows the LC-MS results for the PET degradation intermediate product TPA (terephthalic acid) standard; Figure h shows the LC-MS results for samples after 45 days of co-culturing with JSK8. Detailed Implementation
[0035] The present invention will now be described in detail with reference to specific embodiments. The following specific embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any way.
[0036] Example
[0037] The four plastic sample materials used in this embodiment are: polylactic acid (PLA), model 4032D, NatureWorks, USA; polyhydroxybutyrate (PHB), product number P304, Eckmann; polyethylene terephthalate (PET), model CR-8863, DuPont, USA; and polyethylene (PE), model 5090T, Formosa Plastics, Ningbo. All "v / v" below refers to volume ratio.
[0038] I. Isolation and Identification of Acinetobacter tibetans JSK8
[0039] 1. Sampling
[0040] Water samples were taken at the No. 2 inlet of the Baishamen Wastewater Treatment Plant in Haikou City, Hainan Province in late March 2025.
[0041] 2. Strains Isolation and Purification
[0042] Preparation of liquid enrichment medium: Four sterilized plastic powders (0.5g each): PET (0.5g), PE (0.5g), PLA (0.5g), and PHB (0.5g), all 100-mesh, were mixed as the sole carbon source. 5g of MSM inorganic salt medium (product number: M2356, Shandong Top Biotechnology Co., Ltd.) was added, and the volume was adjusted to 1L with sterile water. The mixture was sterilized at 121℃ and 1MPa for 20 min. For solid screening plates, 20g of agar powder (product number BS195, White Shark) was added to the above mixture.
[0043] Prepare LB medium: 5 g yeast extract (LP0021B, OXOID, UK), 10 g tryptone (LP0042B, OXOID, UK), 10 g NaCl (BS112, White Shark), and bring the volume to 1 L with sterile water. Adjust the pH to 7. Sterilize at 121°C and 1 MPa for 20 min. For LB solid plates, add 20 g agar powder to the above medium.
[0044] Preparation of the colorimetric reagent: Dissolve 4 g of boric acid in 20 mL of deionized water and bring the volume to 100 mL to obtain a boric acid solution; weigh 2.5 g of potassium iodide (KI) and dissolve it in 10 mL of double-distilled water. After dissolution, add 1.27 g of iodine (I) and bring the volume to 100 mL in a volumetric flask to obtain an iodine-potassium iodide solution; mix the boric acid solution and the iodine-potassium iodide solution at a volume ratio of 5:1 to obtain the colorimetric reagent.
[0045] The water sample collected in step 1 was added to a liquid enrichment medium. During the first week, yeast extract (catalog number LP0021B, OXOID, UK) at a concentration of 1 mg / L was added to improve the survival rate of various microorganisms. The medium was incubated in a shaker at 121 r / min and 27℃ for one week at a time. After three enrichment cycles in the liquid enrichment medium, a small amount of the enriched bacterial solution was aspirated and inoculated at 10... -2 10 -3 10 -4 The solution was serially diluted and plated onto solid screening plates. The aforementioned chromogenic reagent was then added to the solid screening plates. If microplastics were degraded, a clear zone would form in the purple solution. The degradation ability of the strain was preliminarily determined based on the clear zone.
[0046] Depend on Figure 1 It can be seen that, with 10 -2 and 10 -4 Strains exhibiting significant degradation effects grew on plates coated with gradient concentration dilutions. The size of the transparent zone was used to determine the degradation effect. -2 The strains in the gradient-diluted plates exhibited a stronger ability to degrade plastics, 10 -3 No degrading strains were observed in the plates coated with gradient dilutions.
[0047] from Figure 1 Strains with larger transparent zones were selected from the solid screening plates that produced transparent zones. A total of 8 strains (numbered ①~⑧) were selected and enriched in liquid enrichment medium for 7 days (strain ② was discarded due to slow growth). -3 The concentration was diluted and coated onto a solid screening plate; growth was observed as shown in the figure. Figure 2 .
[0048] fromFigure 2 Single colonies were picked from each of the seven solid screening plates and enriched in liquid enrichment medium for 7 days. The enriched bacterial solution was then plated onto solid screening plates and incubated at 28°C for 1 day. Colonies were then streaked onto LB agar plates for purification until pure cultures were obtained. The results are as follows: Figure 3 As shown.
[0049] 3. Identification
[0050] Pick them separately Figure 3 Single colonies from LB agar plates were added to sterile PCR tubes containing 10 μL of double-distilled water. The tubes were centrifuged for a few seconds to dissolve the colonies completely. The PCR tubes containing the colonies were then boiled in a 100°C water bath for 10 min, followed by centrifugation at 4000 rpm for 2 min. 2 μL of the supernatant was collected as the DNA template for this strain and used for PCR amplification. Amplification was performed according to the reaction system (Table 1) and amplification conditions, prepared using a PCR instrument.
[0051] PCR amplification of 16S rDNA was performed using universal bacterial primers 27F and 1492R. The primer sequences are as follows:
[0052] 27F (upstream primer): 5′-AGAGTTTGATCCTGGCTCAG-3′ (SEQ ID NO.1)
[0053] 1492R (downstream primer): 5′-TACGGTTACCTTGTTACGACTT-3′ (SEQ ID NO.2).
[0054] Table 1 PCR reaction system
[0055]
[0056] PCR amplification conditions: 97℃ pre-denaturation for 3 min; 98℃ denaturation for 10 s; 56℃ annealing for 30 s; 72℃ extension for 50 s, 26 cycles; final extension at 72℃ for 10 min. Electrophoresis results are as follows. Figure 4 As shown.
[0057] PCR samples with a 1500 bp band were selected and sent to a biotechnology company for sequencing. The nucleotide sequence of the 16S rDNA of strain JSK8 is as follows:
[0058]
[0059] The nucleotide sequence of the 16S rDNA of strain JSK8 was BLASTed and compared on the NCBI website. Figure 5 As shown, the genus and species name of the tested strain, *Acinetobacter* sp., was preliminarily determined, and a phylogenetic tree was constructed using MEGA software with the selection of a type strain, as shown below. Figure 6 As shown, it is most closely related to *Acinetobacter tibetensis*. For further precise identification, whole-genome sequencing and analysis were commissioned to Sangon Biotech (Shanghai) Co., Ltd. (Contract No. BADR2513104HK), during which a phylogenetic tree based on multiple core genes across the entire genome was constructed. Figure 7 The results showed that JSK8 clustered with the Acinetobacter tibetensis type strain Y-23 (GCA_023824315.1) on the same evolutionary branch with 100% bootstrap support, and was clearly differentiated from closely related species such as Acinetobacter johnsonii and Acinetobacter ursingii. Post-QC contamination assessment also showed that 889 reads (8.89%) matched to Acinetobacter tibetensis. Based on these results, strain JSK8 was definitively identified as Acinetobacter tibetensis.
[0060] Acinetobacter tibetensis, or JSK8, was deposited on December 1, 2025, at the China General Microbiological Culture Collection Center (CGMCC), Institute of Microbiology, Chinese Academy of Sciences, No. 3, Courtyard 1, Beichen West Road, Chaoyang District, Beijing, with accession number CGMCC No. 36830 and classified as Acinetobacter tibetensis. It will be referred to as JSK8 below.
[0061] II. Experiment on Degradation of Plastics
[0062] 1. Degradation of plastic particles
[0063] In the plastic particle degradation experiment, the four types of plastic particles used were PHB, PLA, PE and PET, all with a size of 100 mesh, and the amount added per 100 mL of culture medium was 2 g.
[0064] Four parallel experiments were set up. In each experiment, 200 mL of MSM inorganic salt culture medium (product number: M2356, Shandong Top Biotechnology Co., Ltd.) was added to a 500 mL Erlenmeyer flask. PHB / PLA / PE / PET plastic particles were added as the sole carbon source at a mass-volume percentage of 2% g / mL. Bacterial OD was added at a concentration of 5% (v / v). 600 Degradation was performed using JSK8 with a pH of 0.1. The particles were cultured on a shaker at 28 ℃ and 121 r / min for 15, 30, and 45 days. After the culture period, the plastic particles were washed off, filtered, and dried to constant weight. The degradation efficiency (%) was calculated using the weight loss method. The formula for calculating the degradation efficiency (%) is as follows:
[0065] Degradation efficiency (%) = × 100%.
[0066] Depend on Figure 8 It can be seen that strain JSK8 has a degradation effect on PET, PE, PLA and PHB, and the degradation efficiency on PLA and PHB is significantly higher than that on PET and PE.
[0067] The p-NPB method for determining enzyme activity in supernatant: The p-NPB method detects enzymes that can hydrolyze short-chain fatty acid ester bonds, mainly belonging to the class of carboxylic acid ester hydrolases. Examples include esterases, cutinases, lipases, and other serine hydrolases.
[0068] The supernatant obtained by centrifuging the bacterial cultures of different fermentation days (7 days, 14 days, 20 days) at 13000×g for 10 min in the above degradation experiment (7 days, 14 days, 21 days) was directly reacted with the model substrate p-nitrophenol to see if there was esterase or lipase activity.
[0069] Experimental group: 1250 μL 100 mM potassium phosphate buffer pH 8.0 (Catalog No. P885147, Maclean), 150 μL p-NPB substrate working solution (p-nitrophenol (Catalog No. N814718, Maclean) dissolved in isopropanol (1280250101601 Xilong) diluted to a final concentration of 2 mM), 200 μL surfactant Triton X-100 (Catalog No. BS084, White Shark), 200 μL supernatant (7 days, 14 days, 21 days).
[0070] Control group: Sample control: supernatant + buffer (without substrate), used to subtract the color or absorbance of the sample itself; Substrate spontaneous hydrolysis control: buffer + substrate, used to subtract the signal generated by the natural degradation of the substrate in the buffer; Negative control: supernatant deactivated by boiling + substrate.
[0071] Experimental Procedure: Incubate the reaction plate at 30-37°C for 15-30 minutes. Immediately place it in a microplate reader and read the absorbance (A410) at 410 nm. Take kinetic readings every few minutes. Subtract the absorbance (A410) values of the sample control and the substrate spontaneous hydrolysis control from the absorbance (A410) values of the experimental group to obtain the true enzyme activity signal. Results are as follows: Figure 9 As shown, the absorbance (A410) value of the experimental group at 21 days was significantly higher than that at 7 days, and continued to increase over time (the solution turned yellow). The enzyme activity values also increased. Figure 10 As shown, preliminary results indicate that the supernatant from the mixed culture of strain JSK8 with different plastics contains enzymes capable of hydrolyzing the ester bonds of short-chain fatty acids in plastics, mainly belonging to the class of carboxylic acid ester hydrolases. Examples include esterases, cutinases, lipases, and other serine hydrolases.
[0072] 2. Degradation of plastic film
[0073] After determining the degradation effect of the strain on plastic particles, this application aimed to investigate the adhesion of the strain to plastic films and to visualize the degradation effect. The strain JSK8 was cultured using films of four different plastics (PET, PE, PLA, and PHB) as the sole carbon source.
[0074] Culture method: Four types of plastic films (PHB, PLA, PE, and PET) were used, each measuring 2cm × 3cm. In each experiment, 200mL of MSM inorganic salt medium (product number: M2356, Shandong Top Biotechnology Co., Ltd.) was added to a 500mL Erlenmeyer flask, and 5 pieces of PHB / PLA / PE / PET plastic film were added as the sole carbon source. Bacterial OD was added at 5% (v / v). 600 JSK8 with a pH of 0.1 was cultured on a shaker at 28°C and 121 rpm, with the medium replaced every two weeks with 1% fresh MSM inorganic salt to ensure an adequate supply of other growth substances required by the strain. The culture time was determined according to specific experimental needs, as detailed below.
[0075] Four parallel experiments were set up using PE, PET, PLA, and PHB. After culturing for 45 days according to the above method, the samples were analyzed by field emission scanning electron microscopy (SEM). Figure 11 It can be seen that, with Figure 11 Compared to Figure A, the PET film with added strain JSK8 showed the presence of the strain attached, as shown in Figure A. Figure 11 As shown in Figure B; and Figure 11 Compared to Figure C, the PE film with added strain JSK8 showed obvious strain adhesion, and the surface had many pits due to degradation, such as... Figure 11As shown in Figure D; and Figure 11 Compared to the previous image, strain JSK8 showed significant adhesion to PLA plastic film, such as... Figure 11 As shown in Figure F; and Figure 11 Compared to the G diagram, the surface of the PHB film with added strain JSK8 became rough and degraded, forming many tiny cracks, such as... Figure 11 As shown in Figure H.
[0076] To further enhance the reliability of the data, this application also verified the degradation at the molecular level using Fourier transform infrared spectroscopy. Following the aforementioned culture method, four types of plastic films—PET, PE, PLA, and PHB—were cultured for 30 days in media containing and without JSK8. The corresponding experimental groups were named: JSK8+PET, JSK8+PE, JSK8+PLA, and JSK8+PHB. Simultaneously, plastics without added JSK8 served as controls, with the corresponding control groups being: PET, PE, PLA, and PHB. Afterward, the biofilm on the JSK8-colonized polyethylene plastic films was washed away, and infrared observation was performed. The biofilm removal method involved cleaning with 3% hydrogen peroxide, distilled water, and 75% ethanol in an ultrasonic cleaner for 30 minutes. After thorough drying, scanning was performed in the wavelength range of 450-4000 cm⁻¹. -1 The resolution is 1cm. -1 The system was operated in ATR mode. Each spectrum underwent 32 scans. The control group underwent the same treatment. Figure 12 JSK8 treated plastic PET (see...) Figure 12 Figure a in the diagram), PE (see Figure a in the diagram). Figure 12 Figure c in the diagram), PLA (see Figure c) Figure 12 Figure b in the diagram), PHB (see Figure b) Figure 12 In the d-figure (Figure 3), the functional group peaks became blunter and broader, indicating that the functional groups in the plastic were broken down under JSK8 treatment, resulting in a decrease in the content of functional groups and a lower and broader peak. Additionally, the experimental group with added JSK8 showed a peak at 750 cm⁻¹. -1 The shortening and blunting of the crystallization peak at the specified wavelength indicates that the crystallinity of the plastic decreases due to bacterial degradation. This is another strong piece of evidence that this strain possesses degradation capabilities.
[0077] This application compared the degradation efficiency (%) of four plastic films—PHB, PLA, PE, and PET—after 45 days of cultivation with and without the bacterial strain (blank + plastic) with and without the bacterial strain JSK8 (JSK8 + plastic). The results are as follows: Figure 13 As shown, the degradation efficiency of PHB plastic after adding the strain (8.968%) is 7.4 times that of plastic without the strain (1.204%), and the degradation efficiency of PLA plastic after adding the strain (5.667%) is 5.6 times that of plastic without the strain (1.011%).
[0078] To further analyze the generation of products after plastic degradation, this application used liquid chromatography-mass spectrometry (LC-MS) to analyze the mixed culture solution of PET, PE, PLA, and PHB. The LC-MS analysis was performed using a QTRAP 6500 + LC-MS / MS system (AB Sciex).
[0079] LC-MS Analysis of PHB Degradation Products: JSK8 cultured for 45 days in MSM inorganic salt medium with PHB as the sole carbon source (the experimental group contained added JSK8, while the control group did not) according to the above-described culture method. The culture medium (12000 g, 20 min, 4℃) was collected, and the supernatant was obtained. An equal volume of acetonitrile was added to the supernatant, and the mixture was vortexed for 5 min to precipitate the protein. Finally, the mixture was filtered through a syringe using a 0.22 μm filter membrane into a sample vial. The PHB degradation products were analyzed by LC-MS using a HILIC-Z column (3.0 × 150 mm, 2.7 μm). Phase A was 5 mmol / L ammonium acetate aqueous solution (containing 0.1% formic acid), and Phase B was acetonitrile. The flow rate was 0.4 mL / min, and the monitoring wavelength was 240 nm. Elution conditions were as follows: 0-2 min, 90% (v / v) acetonitrile; 2-6 min, linear elution of 90%-60% acetonitrile; 6-9 min, 60% (v / v) acetonitrile; 9-9.1 min, linear gradient of 60%-90% acetonitrile; 9.1-10 min, 90% acetonitrile. Negative ion mode was used, with ESI as the ion source, a curtain gas setting of 35 psi, a temperature of 500℃, a spray gas setting of 50 psi, an auxiliary heating gas setting of 50 psi, and MRM scanning mode. Results are as follows. Figure 14 As shown in Figures a and b, the formation of 3-hydroxybutyric acid, an intermediate product of PHB degradation, was also detected in the sample, and the elution time was consistent with that of the standard, both being 2.35 min.
[0080] LC-MS Analysis of PLA Degradation Products: JSK8 cultured for 45 days in MSM inorganic salt medium with PLA plastic film as the sole carbon source (the experimental group contained JSK8, while the control group did not) according to the above-described culture method. The culture medium (12000 g, 20 min, 4℃) was collected, and the supernatant was obtained. An equal volume of acetonitrile was added to the supernatant, and the mixture was vortexed for 5 min to precipitate the protein. Finally, the mixture was filtered through a syringe using a 0.22 μm filter membrane and transferred to a sample vial. The PLA degradation products were analyzed by LC-MS using a HILIC-Z column (3.0 × 150 mm, 2.7 μm). Phase A was 5 mmol / L ammonium acetate aqueous solution (containing 0.1% formic acid), and Phase B was acetonitrile. The flow rate was 0.4 mL / min, and the monitoring wavelength was 240 nm. Elution conditions were as follows: 0-2 min, 90% (v / v) acetonitrile; 2-6 min, linear elution with 90% - 60% acetonitrile; 6-8 min, 60% (v / v) acetonitrile; 8-8.1 min, linear gradient elution with 60% - 90% acetonitrile; 8.1-12 min, 90% acetonitrile hold for 3 min. Negative ion mode was used, with ESI as the ion source, 35 psi for the curtain gas, 500℃ for the temperature, 50 psi for the spray gas, 50 psi for the auxiliary heating gas, and MRM scanning mode. Results are as follows. Figure 14 As shown in Figures c and d, the formation of lactic acid, an intermediate product of PLA degradation, was detected in the sample, and the elution time was consistent with that of the standard, both being 2.40 min.
[0081] LC-MS Analysis of PET Degradation Products: Following the above cultivation method, JSK8 was cultured for 45 days in MSM inorganic salt medium with PET plastic film as the sole carbon source (the experimental group contained JSK8, while the control group did not). The culture medium was collected (12000 g, 20 min, 4℃), and the supernatant was obtained. The supernatant was adjusted to pH 2.0 with 2 M HCl and extracted with acetonitrile / water (1:1 v / v). The extract was filtered through a 0.22 μm filter into the sample. The degradation products of PET plastic film were analyzed by LC-MS using an XB-C18 100A column (2.1 × 250 mm, 2.6 μm). The mobile phase A was 5 mmol / L ammonium acetate aqueous solution (containing 0.1% formic acid), and phase B was acetonitrile. The flow rate was 0.3 mL / min, and the monitoring wavelength was 240 nm. Elution conditions were as follows: 0-1 min, 10% (v / v) acetonitrile; 1-8 min, linear elution with 10% - 40% acetonitrile; 8-10 min, 40% - 95% (v / v) acetonitrile; 10-10.1 min, linear gradient with 95% - 10% acetonitrile; 10.1-13 min, hold with 10% acetonitrile for 3 min. Negative ion mode was used, with ESI as the ion source, 40 psi for the curtain gas, a temperature of 500℃, 55 psi for the spray gas, 55 psi for the auxiliary heating gas, and MRM scanning mode. Results are as follows. Figure 14 As shown in Figures e and f, the sample exhibits the presence of BHET, a PET degradation intermediate, with a peak elution time consistent with the standard (7.02 min). Simultaneously, the sample also shows the presence of TPA, another PET degradation intermediate, with a peak elution time consistent with the standard (2.18 min). Figure 14 As shown in the g-plot and h-plot.
[0082] It should be noted that no clear degradation intermediates were detected by LC-MS analysis in the PE degradation experiment. The main reason is that the polyethylene molecular chain is highly inert and hydrophobic, and the degradation intermediates are difficult to be effectively captured by LC-MS. Therefore, no LC-MS analysis results of its degradation products were presented.
[0083] In summary, based on the degradation substrate spectrum, *Acinetobacter tibetans* JSK8 exhibits the best versatility, covering PHB, PLA, PET, and PE, encompassing both traditional and emerging plastics. Regarding degradation efficiency data, *Acinetobacter tibetans* JSK8 provides approximately 10% PHB degradation data after 45 days, showing a significant improvement (8-fold) compared to the sterile control. In terms of application potential, *Acinetobacter tibetans* JSK8 operates under mild conditions and requires no pretreatment, making it most suitable for practical, low-cost applications.
[0084] Obviously, the above embodiments of the present invention are merely examples to illustrate the present invention more clearly, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all implementation methods here. Any obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. Acinetobacter tibetans JSK8, characterized in that, It was deposited on December 1, 2025, at the China General Microbiological Culture Collection Center (CGMCC) with accession number CGMCC No. 36830 and classified as Acinetobacter tibetensis.
2. The Acinetobacter tibetans JSK8 according to claim 1, characterized in that, The nucleotide sequence of the 16S rDNA of Acinetobacter tsuifolia JSK8 is shown in SEQ ID NO.
3.
3. The application of Acinetobacter tibetans JSK8 as described in claim 1 in the degradation of plastics, characterized in that, The plastics include four types: polyhydroxybutyrate (PHB), polylactic acid (PLA), polyethylene terephthalate (PET), and polyethylene (PE).
4. The application according to claim 3, characterized in that, The application involves culturing Acinetobacter tsuifolia JSK8 with plastic on a shaker at 28 °C and 121 r / min to achieve degradation.
5. The application according to claim 4, characterized in that, Acinetobacter tsui JSK8 was cultured in MSM inorganic salt medium using plastic as the sole carbon source at a bacterial concentration of 5%. The bacterial OD... 600 The value is 0.1.
